2003 Survey of the Florida Caladium Tuber Production Industry - Zhanao Deng; Brent K. Harbaugh; Rick K. Schoellhorn; R. C. Andrews (EDIS, 2009)
Revised! ENH-1007, a fact sheet by Z. Deng, B.K. Harbaugh, R.K. Schoellhorn, and R.C. Andrews, reports the results of a survey of Florida caladium growers and industry to gather demographic information, to understand the industry’s needs, and to identify the leading cultivars grown commercially in Florida. Published by the UF Department of Environmental Horticulture, December 2008.